Psychedelics in developmental stuttering to modulate brain functioning: a new therapeutic perspective? - Pasculli, Giuseppe; Busan, Pierpaolo; Jackson, Eric S.; Alm, Per A.; De Gregorio, Danilo; Maguire, Gerald A.; Goodwin, Guy M.; Gobbi, Gabriella; Erritzoe, David; Carhart-Harris, Robin L. (Frontiers in Human Neuroscience, 2024)
Developmental stuttering (DS) is a neurodevelopmental speech-motor disorder, characterized by symptoms such as blocks, repetitions, and prolongations. Persistent DS often has a significant negative impact on quality of life, and interventions for it have limited efficacy. Here we briefly review existing research on the neurophysiological underpinnings of DS -specifically, brain metabolic and Default Mode/Social-Cognitive Networks (DMN/SCN) anomalies-arguing that psychedelic compounds should be evaluated for DS treatment. The neural background of DS is likely to be heterogeneous, some contribution from genetically determinants of metabolic deficiencies in the basal ganglia and speech-motor cortical regions are thought to play a role, possibly resulting in a cascade of events contributing to impairments in speech motor execution. In persistent DS, the difficulties of speech are often linked to a series of associated aspects such as social anxiety and social avoidance. In this context, the SCN and DMN (also influencing a series of fronto-parietal, somato-motor, and attentional networks) may have a role. Interestingly, brain metabolism and SCN/DMN connectivity can be modified by psychedelics, which have shown positive effects in psychiatric conditions (e.g. depression, post-traumatic stress disorder, etc.) associated with psychological constructs such as rumination and social anxiety, that also tend to be present in persistent DS. To date, while there have been no controlled trials on the effects of psychedelics in DS, anecdotal evidence suggests beneficial effects of psychedelics for stuttering and its associated characteristics. Hence, we suggest that psychedelics could be investigated for a potential beneficial impact in DS.